WordPress Mobile Web Development: Beginner's Guide - Mccollin, Rachel; Mccollin, Rachel (Packt Publishing, 2012)
Beginner's Guide. If you have dabbled in WordPress or been working with it for years, and want to build mobile or responsive themes or sites, this book is for you. Even if you can't write a line of code, the first few chapters will help you create a simple mobile site. But to get the most from the book, you will need a good understanding of HTML, CSS and WordPress itself. This book is for owners of self-hosted WordPress sites, not sites hosted at wordpress.com.